Problem Posing Learning Model to Improve Critical Thinking Ability - Wati Susanti (Jurnal Report of Biological Education, 2020)
This study aims to determine the effect of problem posing learning models on improving students' critical thinking skills. Subjects in the study were students of SMP Negeri 6 Sukabumi City VII class even semester with a total of 38 people. The method used in this study is a weak experimental method with The One Group Pre-test and Post-test Design research design. The instrument used was a question of critical thinking skills in the form of a description. Indicators of critical thinking skills captured from the instrument are focusing questions, answering questions, observing and considering the results of observations, making and considering the results of decisions, identifying terms and considering definitions. The results showed that students' critical thinking skills after learning using the problem posing model increased from an average of 51.34 initial tests increased to 84.37 greater than the Minimum Completion Criteria 75, and the results of hypothesis testing of the final test data, the value of Zcount was obtained of 9.56 is greater than the value of Ztable of 1,645. This shows that H0 was rejected. Increased students' critical thinking skills were also seen from the value of N-Gain of 0.68 and N-Gain on each indicator. In this study, there is the influence of the problem posing learning model on improving students' critical thinking skills.